THE EVALUATION OF INTERNAL CONTROL ON SALES AND CASH RECEIPT ACCOUNTING SYSTEM (Case Study at PT PG Candi Baru Sidoarjo) - Nur Muflikhah (Jurnal Administrasi Bisnis, 2014)
One of the most important information that companies need is the information regarding the sales. Sales activities consist of selling goods and services, therefore sales will provide revenue contribution for the company. Sales are potential activities that contribute to generate incomes for the company. Following this assumption, having a good accounting system is important. This study aims to evaluate sales and cash receipt accounting system applied in PT PG Candi Baru Sidoarjo, and to scrutinize how the company implements the internal control. Key word :Internal Control, Sales Accounting System, Cash Receipt Accounting System Salah satu informasi yang dibutuhkan perusahaan adalah informasi mengenai penjualan. Aktivitas penjualan terdiri atas menjual barang dan jasa, kemudian penjualan akan mendapatkan kontribusi berupa pendapatan. Penjualan adalah aktivitas yang potensial karina berkontribusi untuk mendapatkan pendapatan bagi perusahaan. Dengan asumsi ini, memiliki sistem akuntansi yang baik sangat diperlukan bagi suatu perusahaan. Studi ini bertujuan untuk mngevaluasi sistem akuntansi penjualan dan penerimaan kas yang diterpakan pada PT PG Candi Baru Sidoarjo dan untuk menyempurnakan pengendalian intern perusahaan. Kata kunci :Pengendalian Intern, Sistem Akuntansi Penjualan, Sistem Akuntansi Penerimaan Kas